Improving the ballistic characteristics and the maintenance of protective ballistic vests - Radonjić, Vojkan M.; Jovanović, Danko M.; Živanović, Goran Ž.; Resimić, Branko V. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The work presents research of the materials necessary for the maintenance of protective ballistic vests. In this paper is proposed a new construction design with modern materials for ballistic inserts producing. This paper also presents the results of laboratory tests of ballistic cartridges with new materials. Based on the test results, it can be concluded, the proposed technical solution for making ballistic inserts adequately meets current standards. Introduction The introduction explains the purpose of the armor and the history of models of protective vests for us. The aim of this study is to improve the structure of existing protective ballistic vests, to propose a new mechanism construction ballistic cartridge, and to examine the validity of the proposed design based on the results of laboratory tests. Existing structural solution In the above is explained existing model of protective ballistic vests that are in use in our army. Structural solution, composition of these models and used materials for ballistic inserts are shown. It is explained reactions (resistance) of the ballistic inserts materials, when bullets pass through them. Time resource of the materials for current models of body armor is expired. According to this fact, it is started research work, with intention to extend the current time resource. Standards of ballistic protection It is shown requirements for standards of ballistic protection level III and III A. Also are explained standards requirements and under what circumstances is performed laboratory testing of protective ballistic vests. Modern ballistic materials The characteristics and description of the currently most advanced materials for ballistic inserts that meet the requirements of the protection level III A are explained. The comparison of material characteristics Dyneema producer of the first models to contemporaneously under the symbol SB 51 is performed. Based on the characteristics of the analyzed material, in the research is used material Dyneema SB 51. Proposal of a new structural solutions In papaer is proposed a new construction solution from the cartridge ballistic material Dyneema SB 51, which should satisfy the protection level III A. In addition, we prepare two new samples of material combinations SB 21 and old material and material SB 21. With such samples the ballistic protective inserts started with laboratory tests. Analysis of test results In tables we show results of testing the samples of ballistic inserts. The conclusion from the performed tests is all samples meet the requirements of the current standards. With observing other aspects of the samples, we give the proposal for maintain ballistic inserts with implementation of material Dyneema SB 51. The reason for this proposal is given in conclusion. Conclusion The aim of the research conducted was to get results that will explicitly show the best material for making ballistic inserts in the technological process of maintenance of protective ballistic vests. ﻿Conducted research in the economics analysis and the laboratory tests showed that the ballistic inserts made of a material Dyneema SB 51 to the proposed construction solutions to meet the requirements of Figure 3 standard NIJ 0101. ﻿04 and allow: -          better ballistic properties of the protection level IIIA, -          the long time resource, up to 10 years, -          reduce the number of layers of sheets of ballistic materials for making cartridges, -          a small amount of material for making ballistic inserts for the required level of protection, -          easier to cut sheets of ballistic material during cutting and making ballistic inserts, -          less time developing new ballistic inserts, -          less money for making balčističkih cartridges for the required level of protection.
Keywords: Dyneema; Vest; protective; Materials; inserts